Od hiše do niše Razvoj kuhinje v Vipavski dolini - Ledinek Lozej, Špela (Ethnologica - Dissertationes, 2015)
The kitchen is the core~it is the heart of the home. A major part of our daily routine takes place in the kitchen. In addition to being a place for food preparation, the kitchen also defines our lifestyle and social status. In the 20th century, the kitchen, its practices and representations were changing. The form, use and purpose of the kitchen were connected to general and specific (micro-)regional economic, social, demographic, cultural and ideological circumstances, and after all also socio-economic conditions of the household. This book ('From the main place to dwell to a working cell: Development of the kitchen in the Vipava Valley') presents the formal development of the kitchen in the Vipava Valley in the 20th century regarding the changes in kitchen practices and the image of the kitchen.